Body dissatisfaction and its association with domains of physical activity and of sedentary behavior in a sample of 15,632 adolescents - Tebar, William R. [UNESP] (2020)
Body image is widely related to behavioral factors in adolescents and negative levels has been associated to poor physical and mental health. This study analyzed the association of physical activity and sedentary behavior with body dissatisfaction in adolescents. Data from 15,632 adolescents between 11 and 17 years from the Brazilian National Scholar Health Survey - PeNSE 2015 were analyzed. Body dissatisfaction was self-reported. Sedentary behavior was assessed by hours in television (TV) viewing and in overall sitting behaviors. Physical activity was assessed by amount of time in domains of active commuting, physical education classes at school, and physical activities outside the school. Analyses were adjusted by age, ethnicity, body mass index, and scholarity of mother. Body dissatisfaction prevalence was 18.5%, being higher in girls than boys (24.2 vs. 12.7%, p < 0.001). Female gender (OR = 2.35), higher age-group (OR = 1.64), high scholarity of mother (OR = 1.43), and had overweight/obesity (OR = 2.38/4.81) were positively related to body dissatisfaction. Higher sedentary time was associated with body dissatisfaction in adolescents when compared to less than 2 h/day of sedentary time (OR varying from 1.45 to 2.14). Physical activity was negatively associated with adolescent body dissatisfaction in all assessed domains, with odds ratio varying from 0.66 to 0.89. Body dissatisfaction showed an independent association of with total sedentary behavior (positively) and with different domains of physical activity (negatively) in a large scholar sample of Brazilian adolescents.